Diseño e implementación de procedimientos contables - financieros y administrativos en Hansa Cía. Ltda. - Arias Quimba, Tania Marisol (2006)
Today, the phenomenon of globalization and free trade agreements such as the Free Trade Area of the Americas FTAA, the Free Trade Agreement NAFTA, among other factors have caused rapid changes in both the global economy and in the commercial market growth in country, which affects and involves Ecuadorian companies, and are required to establish competitive strategies, one of which may be to implement a plan of continuous improvement of products and processes, in addition to training and development its human resources, which is the cornerstone of an organizational culture of quality, these are the only organizations that may have a market share that will allow them to receive economic benefits and remained in time.